2015
DOI: 10.4049/jimmunol.1401334
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variation in Aicardi–Goutières Syndrome Explained by Cell-Specific IFN-Stimulated Gene Response and Cytokine Release

Abstract: Aicardi–Goutières syndrome (AGS) is a monogenic inflammatory encephalopathy caused by mutations in TREX1, RNASEH2A, RNASEH2B, RNASEH2C, SAMHD1, ADAR1, or MDA5. Mutations in those genes affect normal RNA/DNA intracellular metabolism and detection, triggering an autoimmune response with an increase in cerebral IFN-α production by astrocytes. Microangiopathy and vascular disease also contribute to the neuropathology in AGS. In this study, we report that AGS gene silencing of TREX1, SAMHD1, RNASEH2A, and ADAR1 by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…Upregulation of both transcripts was confirmed by RT–qPCR, and ELISA of culture supernatants from all six Rnaseh2b −/− lines demonstrated significantly increased CCL5 and CXCL10 secretion (Fig 3D and E, and Appendix Fig S2B). Notably, these cytokines have previously been implicated in AGS neuroinflammation in humans (van Heteren et al , 2008; Takanohashi et al , 2013; Cuadrado et al , 2015). We therefore concluded that impaired RNase H2 activity in vitro and in vivo results in a similar inflammatory response to that observed in patients with AGS, and like for Trex1 deficiency (Gall et al , 2012) is present in non‐immune cells.…”
Section: Resultsmentioning
confidence: 97%
“…Upregulation of both transcripts was confirmed by RT–qPCR, and ELISA of culture supernatants from all six Rnaseh2b −/− lines demonstrated significantly increased CCL5 and CXCL10 secretion (Fig 3D and E, and Appendix Fig S2B). Notably, these cytokines have previously been implicated in AGS neuroinflammation in humans (van Heteren et al , 2008; Takanohashi et al , 2013; Cuadrado et al , 2015). We therefore concluded that impaired RNase H2 activity in vitro and in vivo results in a similar inflammatory response to that observed in patients with AGS, and like for Trex1 deficiency (Gall et al , 2012) is present in non‐immune cells.…”
Section: Resultsmentioning
confidence: 97%
“…52,53 We recently reported enhanced proinflammatory activation in macrophages from mice lacking Trex1, 22 and the release of cytokines has been attributed to phenotypic variations in patients with Aicardi-Goutières syndrome. 54 Mutations that lead to activation of innate immunity by inducing the secretion of type I IFN collectively may represent "interferonopathies", 55 disorders that are characterized by neurologic and dermatologic features provoked by autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients with AGS exhibit later onset of symptoms, and lack abnormalities on brain imaging or CSF . Numerous patients with RNASEH2B mutations and AGS type 2 (AGS2) have a milder phenotype with lower childhood mortality and better preservation of function .…”
mentioning
confidence: 99%